2020
DOI: 10.3389/fphys.2020.00815
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Contractility Measurements Reveal Large Atrioventricular and Subtle Interventricular Differences in Cultured Unloaded Rat Cardiomyocytes

Abstract: The chambers of the heart fulfill different hemodynamic functions, which are reflected in their structural and contractile properties. While the atria are highly elastic to allow filling from the venous system, the ventricles need to be able to produce sufficiently high pressures to eject blood into the circulation. The right ventricle (RV) pumps into the low pressure pulmonary circulation, while the left ventricle (LV) needs to overcome the high pressure of the systemic circulation. It is incompletely underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
4
13
0
Order By: Relevance
“…Our study demonstrates that in the healthy heart, CM from LV, RV, and IS differ in morphology, Ca 2+ handling, and contractile function. We have shown that the contractile function of IS myocytes is closer to that of LV and distinct from the contractile function of RV, according to [37]. In mechanically non-loaded conditions, CM from RV had a smaller amplitude of sarcomere shortening and shorter times of shortening and relaxation than IS, which agrees with [37].…”
Section: Interventricular Differences In the Healthy Heartsupporting
confidence: 75%
See 1 more Smart Citation
“…Our study demonstrates that in the healthy heart, CM from LV, RV, and IS differ in morphology, Ca 2+ handling, and contractile function. We have shown that the contractile function of IS myocytes is closer to that of LV and distinct from the contractile function of RV, according to [37]. In mechanically non-loaded conditions, CM from RV had a smaller amplitude of sarcomere shortening and shorter times of shortening and relaxation than IS, which agrees with [37].…”
Section: Interventricular Differences In the Healthy Heartsupporting
confidence: 75%
“…We have shown that the contractile function of IS myocytes is closer to that of LV and distinct from the contractile function of RV, according to [37]. In mechanically non-loaded conditions, CM from RV had a smaller amplitude of sarcomere shortening and shorter times of shortening and relaxation than IS, which agrees with [37]. However, we have not found any significant differences in the amplitude of sarcomere shortening between CM from LV and RV as observed in rodents in earlier studies [37][38][39].…”
Section: Interventricular Differences In the Healthy Heartmentioning
confidence: 94%
“…This increased the throughput of these measurements considerably. Wright et al shows that this improves the data quality, enabling inter-preparation and within-preparation statistical correction which results in more reliable hypothesis testing [ 13 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current validation was performed on rat cardiomyocytes, but Wright et al also shows its potential in mouse, guinea pig and human cardiomyocytes [ 13 ]. The increased throughput reduces the number of animals needed, the standardized conditions reduce variability between animals, and the increased number of measurements per drug result in more reliable outcomes [ 12 , 13 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation